DESCRIPTION OF THE ADMINISTRATIVE GOVERNANCE OF THE TURKESTAN REGION IN LEGISLATIVE DOCUMENTS OF THE RUSSIAN GOVERNMENT - Jumayev U. X. (Modern American Journals, 2026)
This text analyzes the source value of legislative and official record-keeping documents produced during the period of the Russian Empire for studying the history of the Turkestan region. Normative acts—particularly statutes and instructions related to the governance of Turkestan—are interpreted as a primary evidentiary layer that makes it possible to reconstruct the evolution of the region’s administrative management and the legal status of the local population. In addition, the service records (formular lists) of colonial administrative officials, reports by senior authorities, and materials from senatorial inspections (F.K. Girs, K.K. Palen) are presented as reliable sources illuminating the region’s economy, tax policy, land–property relations, and the mechanisms of bureaucratic governance. Using the reports of K.P. Kaufman as an example, the content of the land-tax reform project, the distribution of the tax burden, and issues of fiscal interest are examined. In conclusion, although the imperial legislative documents served to consolidate the colonial position in Turkestan, it is substantiated that they possess high source value for analyzing the administrative and legal practices of the period.
Keywords: Turkestan region, Russian imperial legislation, normative legal acts, colonial governance, “Regulations,” official reports, formular lists, senatorial inspection, land and tax policy, administrative evolution.